2012
DOI: 10.1016/j.ajpath.2011.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated Gene Transfer of TGF-β1 to the Renal Glomeruli Leads to Proteinuria

Abstract: The mechanism of proteinuria in many common kidney diseases involves glomerular hemodynamic effects and local expression of angiogenic, fibrogenic, and vasoactive factors. Transforming growth factor (TGF)-β has been associated with many diseases involving proteinuria and renal fibrosis. TGF-β has been shown to induce podocyte dedifferentiation in vitro, but its in vivo effects on the glomerular filtration barrier are not well described. In this study, we used an adenovirus vector to transfer active TGF-β1 to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
5
14
0
Order By: Relevance
“…In a recently described model of TGF-β overexpression in the glomerulus using an adenovirus [37], we found that ANGPT1 and ANGPT2 were both upregulated in the glomeruli from animals exposed to AdTGFB1, which is similar to observations by Campean et al [38] in the Thy 1.1 model of glomerular injury. In unstimulated podocytes, we found no expression of TEK, but exposure to TGF-β increased TEK expression.…”
Section: Communication Between Components Of the Filtration Barriersupporting
confidence: 89%
See 1 more Smart Citation
“…In a recently described model of TGF-β overexpression in the glomerulus using an adenovirus [37], we found that ANGPT1 and ANGPT2 were both upregulated in the glomeruli from animals exposed to AdTGFB1, which is similar to observations by Campean et al [38] in the Thy 1.1 model of glomerular injury. In unstimulated podocytes, we found no expression of TEK, but exposure to TGF-β increased TEK expression.…”
Section: Communication Between Components Of the Filtration Barriersupporting
confidence: 89%
“…We were able to block the effects of TGF-β on podocytes in culture with small interfering RNA directed against TEK, or with antibodies directed against TEK or ANGPT1. We hypothesized that TGF-β is required for podocyte dedifferentiation either as a direct cofactor or through the induction of TEK receptors on podocytes [37].…”
Section: Communication Between Components Of the Filtration Barriermentioning
confidence: 99%
“…We chose recombinant adeno-associated virus (rAAV) to deliver shRNA against rat STIM1 to rat kidney, because the in vivo rAAV/shRNA delivery system has been well developed in rats. [51][52][53][54] The rAAV-carried eGFP-tagged shRNA against rat STIM1 (rAAV-eGFP-shStim1) was administered to rats by tail vein injection. An rAAV1/2 encoding an eGFP-tagged scrambled shRNA served as a control.…”
Section: In Vivo Knockdown Of Stim1 In Mcs Increased Col IV Protein Ementioning
confidence: 99%
“…Furthermore, accumulation of TGF-␤ and its pathogenic roles in primary focal segmental glomerulosclerosis, progressive glomerulosclerosis, and diabetic nephropathy have been reported (26,28). In addition, adenovirus-mediated TGF-␤1 gene transfer to kidney glomeruli leads to proteinuria in rats (29). It has been reported recently that podocyte-specific overexpression of TGF-␤ induces segmental glomerulosclerosis with dysfunction in endothelial cells and podocyte depletion (30).…”
mentioning
confidence: 99%